Jake Drake, class clown - Clements, Andrew, 1949-; Frazee, Marla; Pedersen, Janet (New York : Aladdin Paperbacks, 2007)
"Miss Bruce is the new student teacher in second grade, and she never smiles. Never. But when Jake cracks up the class during a spelling bee, he sees the tiniest hint of a smile at the corner of her mouth. Suddenly, Jake has a new mission in life: to be so funny that even Miss Bruce will laugh!"--P. [4] of cover.
Keywords: Student teachers -- Fiction; Teachers -- Fiction; Schools -- Fiction